Pengaruh Tenaga Kerja, Modal Dan Luas Lahan Terhadap Produksi Usaha Tani Tebu Di Kecamatan Ngadiluwih Kabupaten Kediri - Moh Rozi; Abu Talkah; Ahsin Daroini (Manajemen Agribisnis: Jurnal Agribisnis, 2020)
The purpose of this study are: (1) to know the effect of land area to the production of sugarcane farming business at Ngadiluwih-Kediri; (2) To know the effect of capital on sugarcane farm production at Ngadiluwih-Kediri; (3) To know the influence of labors on the production of sugarcane farming business in Ngadiluwih-Kediri; (4) to know the influence of land area, capital and labors simultanously to production of sugarcane farming business in Ngadiluwih-Kediri; (5) to know the most dominant influence of variable land area, labor and capital to the production of sugarcane farming business in Ngadiluwih Kediri. Population used in this research is sugar cane farmer in Ngadiluwih-Kediri Regency. This study uses Proportional Stratified Random Sampling. This technique is used when the population has non-homogeneous elements and is taken randomly, but proportionately. By utilizing Slovin formulations in the sampling with the accuracy of 10% obtained 95 respondents. This study uses instruments that have been developed by previous researchers. The instrument used is a questionnaire with Likert scale 5 for each research variable. The results showed that: (1) Labor has a positive influence on the production of sugarcane farming in Ngadiluwih Kediri Regency. (2) Capital significantly has a positive influence on the production of sugarcane farming in Ngadiluwih Kediri Regency. (3) Land area significantly has a positive influence on the production of sugarcane farming business in Ngadiluwih Kediri Regency. (4) Together labor, capital and land area have a positive effect on the production of sugar cane farming business in Ngadiluwih Kediri Regency. (5) The result of dominance test analysis to know the effective contribution shows that capital has the most dominant contribution in influencing the production of sugarcane farming business in Ngadiluwih Kediri Regency.